2016
DOI: 10.1590/0074-02760150453
|View full text |Cite
|
Sign up to set email alerts
|

Primary dengue haemorrhagic fever in patients from northeast of Brazil is associated with high levels of interferon-β during acute phase

Abstract: Dengue is an acute febrile disease caused by the mosquito-borne dengue virus (DENV) that according to clinical manifestations can be classified as asymptomatic, mild or severe dengue. Severe dengue cases have been associated with an unbalanced immune response characterised by an over secretion of inflammatory cytokines. In the present study we measured type I interferon (IFN-I) transcript and circulating levels in primary and secondary DENV infected patients. We observed that dengue fever (DF) and dengue haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Using published criteria for clinical assessment (Tomashek et al 2018), 27.7% of our patients with PI qualified as severe thrombocytopenia and 38.8% had moderate thrombocytopenia, without significant differences compared with SI (Table 4). We observed a decrease in albumin, along with elevated alanine transaminase (ALT) and aspartate transaminase (AST) in both PI and SI (Table 4) denoting liver inflammation, which has been associated with severity (Oliveira et al 2016, Posadas-Mondragón et al 2017; however, there were no cases of acute hepatitis marked by >10 times ALT increase, unlike in other studies (Souza et al 2004). It has been reported that Ca 2+ levels correlate with disease severity, with hypocalcemia being more prevalent in DHF than in DF (Constantine et al 2014).…”
Section: Discussionmentioning
confidence: 64%
“…Using published criteria for clinical assessment (Tomashek et al 2018), 27.7% of our patients with PI qualified as severe thrombocytopenia and 38.8% had moderate thrombocytopenia, without significant differences compared with SI (Table 4). We observed a decrease in albumin, along with elevated alanine transaminase (ALT) and aspartate transaminase (AST) in both PI and SI (Table 4) denoting liver inflammation, which has been associated with severity (Oliveira et al 2016, Posadas-Mondragón et al 2017; however, there were no cases of acute hepatitis marked by >10 times ALT increase, unlike in other studies (Souza et al 2004). It has been reported that Ca 2+ levels correlate with disease severity, with hypocalcemia being more prevalent in DHF than in DF (Constantine et al 2014).…”
Section: Discussionmentioning
confidence: 64%
“…However, a larger number of studies have explored serum IFN levels in dengue patients. For type I IFNs, the serum level of IFN- β was significantly higher in primary DHF patients than in patients with dengue fever [ 19 ], suggesting that high levels of IFN- β might accompany a worsened progression of the disease. However, the other type 1 IFN, IFN- α , displayed an opposite phenomenon.…”
Section: Initial Immune Response To Dengue In Pregnant Womenmentioning
confidence: 99%
“…Therefore, a high level of type II IFNs is needed for the treatment of dengue patients in clinics. It has been also reported that, during acute infection, higher serum levels of IFN- β [6.69 (0.15~34.9) pg/mL] were found in DHF patients with primary infection than that [2.35 (0~10.1) pg/mL] in the DHF patients with secondary infection [ 19 ]. To this point, the serum IFN- β level of dengue patients was not associated with dengue progression.…”
Section: Initial Immune Response To Dengue In Pregnant Womenmentioning
confidence: 99%
“…Despite being the only natural vertebrate hosts for DENV, non-human primates are not preferred as an animal model for experimental DEN infection, failing to show signs of the disease as observed in humans (Clark et al 2013). The absence of a suitable animal model that successfully replicates the disease as it occurs naturally not only hampers the development of efficient vaccines and therapeutics, but also hinders a better understanding of the viral mechanisms of immunopathogenesis (Oliveira et al 2016). Although some DENV strains induce limited viremia in some mouse strains, the overwhelming majority of immunocompetent mouse models do not present with clinical signs of DENV infection (Sarathy et al 2015).…”
mentioning
confidence: 99%